Molecular dynamics simulation of microstructure evolution and heat dissipation of nanoscale friction. (June 2017) - Chen, Kai; Wang, Liangbi; Chen, Yitung; Wang, Qiuwang
Highlights: Details of microstructure evolution of the interface are shown. Deformation in the mixing layer is the source of friction heat. Sliding velocity has great impact on the growth of mixing layer and the temperature rise. The growth dynamics of mixing layer is proposed. Abstract: The atomic scale interfacial microstructure evolution and heat dissipation process in nanoscale friction are investigated by 3D non-equilibrium molecular dynamics (MD) simulations. Two Ni blocks of different orientations are built to simulate the self-mate friction. The embedded atom (EAM) potentials are employed in these simulations. The microstructure evolution is observed. The temperature and velocity profiles along the height direction, which is perpendicular to the direction of motion, are calculated under sliding velocity. The heat dissipation process is studied. The effect of sliding velocity is also obtained. The results show that extensive plastic deformation and temperature rise occur in the interface. Atomic scale mechanical mixing and generation of mixing layer are observed in the regions near the contact interface. The sliding velocity has great impact on temperature rise. The study of the growth dynamics of mixing layer also sheds light on the formation process of mixing layer.